If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + 4 = 48 Reorder the terms: 4 + 8x = 48 Solving 4 + 8x = 48 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 8x = 48 + -4 Combine like terms: 4 + -4 = 0 0 + 8x = 48 + -4 8x = 48 + -4 Combine like terms: 48 + -4 = 44 8x = 44 Divide each side by '8'. x = 5.5 Simplifying x = 5.5
| x+x+x-4-3-2=12 | | 6-9x+4y=0 | | 8x-4=48 | | 4(k+1)=16 | | 78=-0909089 | | 32534-57908= | | x+(-8)=6 | | 32534-57908=89 | | 2y-4=8 | | 54x-788767= | | p(x)=x^3-5x^2-17x+21 | | 2y=8x+10 | | 12221-6756-8=67 | | y(y-3)=4 | | 3x^2+x^2-8x+4=0 | | z^2=15-2z | | n+9/3=14 | | 9y+1=45+2y | | 8x^2+6x^2+2x+5x= | | 78=6x | | -7+2(2n-1)=-31-7n | | 5t-17.2=16.3 | | x+7+x=15 | | s=2B+F | | 10=b(2/3) | | (6u+1)-(2u+5)= | | x+7+x= | | p(x)=x^3+7x^2+4x-12 | | 6x+6+15x+15=4 | | 29.1=3.6a+7.5 | | x^2+3x-650=0 | | 2(3x+3)+3(5x+5)=3 |